Desenvolvimento Floral e Produtividade de Plantas de Soja Tratadas com Benziladenina - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
The productivity of soybean plants can be increased by adopting practices to reduce the abortion of flowers and / or pods. The amount of flowers that originate the pods is a key factor for obtaining high yields. The objective of this study was to evaluate the morphophysiological effect of benzyladenine in the abortion of reproductive structures of soybean plants. The work was conducted at the Panorama Farm in the municipality of Ipameri, Goiás. Soy "Pioneer 98Y12 RR" sown in November, during the period of the rainy season. The experiment was conducted in a randomized block design with five treatments: 0; 100; 200; 300 and 400 mg L1 benzyladenine with application in the V6 stage spray volume of 200 L ha-1 and five replications. Experimental plots of 3 x 2 m and about 90 plants operated in a space of 0.5 m between rows and 10 plants per meter. The application of benzyladenine provided an increase in weight of 100 grains, number of grains per plant, grain diameter and promoted an increase of 35% in productivity of soybean plants. The results indicate that the application of benzyladenine is promising practice in soybean cultivation.
Keywords: Glycine max L.; Regulador de crescimento; Abortamento; Glycine max L.; Regulator of growth; Abortion; CIENCIAS AGRARIAS